GAMBARAN PENGELOLAAN LIMBAH ARSIP MEDIS PADAT DI RSUD DR RADEN SOEDJONO SELONG TAHUN 2024 - Riopandi, Lalu Ahmad; Fathurrahman; Slamet Mardiyanto Rahayu; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; RACHMAN, Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2024)
Solid medical waste is one type of hazardous waste produced by hospitals and has the potential to pose serious risks to human health and environmental pollution if not managed properly. Management of this waste includes a series of processes that must be carried out systematically and in accordance with applicable regulatory standards, such as sorting, collection, temporary storage, transportation, to final destruction. This study aims to evaluate or describe the solid medical waste management system at RSUD dr. Raden Soedjono Selong in 2024. This study is a descriptive study with a quantitative approach, in the form of direct observation and documentation. The results of the study showed that the management of solid medical waste at RSUD dr. Raden Soedjono Selong, the average value of solid medical waste management from 35 days of observation was 19, this proves that the management of solid medical waste with an average value of 19 out of 16 means that the management of solid medical waste at RSUD dr. Raden Soedjono Selong "is optimal".